Optimization of carotenoids and antioxidant activity of oils obtained from a co-extraction of citrus (Yuzu ichandrin) by-products using supercritical carbon dioxide. (November 2017) - Ndayishimiye, John; Chun, Byung Soo
Abstract: The processing of citrus fruits leaves massive by-products. Those by-products which are considered as wastes contain a wide range of healthy bioactive compounds where carotenoids are among of them. This work aimed to study the optimum supercritical carbon dioxide (SC-CO2 ) extraction conditions for maximization of carotenoid content and antioxidant activity for citrus by-products, using response surface methodology so that those by-products can not only be valorized effectively but also to reduce disposal problems. The effects of pressure, temperature, and mixing ratio (citrus peel-to-citrus seed mass ratio) on the recovery of carotenoids and antioxidant activity were studied. A second-order polynomial model showed a suitable fitting of the experimental values regarding the carotenoid content (R 2 = 0.9974, p < 0.05) and antioxidant activity (DPPH (R 2 = 0.9919, p < 0.05) and ABTS assay (R 2 = 0.9885, p < 0.05)). An optimization and validation study was performed and the optimum extraction conditions were 25.196 MPa, 44.88 °C and 1.91 for carotenoid content, 29.960 MPa, 41.08 °C and 1.52 for DPPH assay and 29.983 MPa, 43.14 °C and 1.50 for ABTS assay, respectively, for pressure, temperature and mixing ratio. The corresponding predicted values were 1.983 mg g −1 oil for carotenoid content, 0.762 mg cm −3 for DPPH, and 1.220 mg cm −3 for ABTS assay. The predicted and the experimental values were well in agreement, thus affirming the adequacy and validity of the predicted models. Overall, the combination of citrus by-products could yield the oils with good bio-activity and this could be a new valorization method. Graphical abstract: Highlights: The effects of extraction conditions on the SC-CO2 extraction of citrus by-products were studied. Optimum extraction conditions for carotenoids and antioxidant activity were established. The predicted and experimental values were in good agreement. The combination of citrus by-products increased the carotenoid content of oils. The combination of citrus by-products increased the antioxidant activity of oils.